Growth hormone stimulates lipolysis in mice but not in adipose tissue or adipocyte culture - Zhao, Lidan; Jiang, Honglin (Frontiers in Endocrinology, 2023)
The inhibitory effect of growth hormone (GH) on adipose tissue growth and the stimulatory effect of GH on lipolysis are well known, but the mechanisms underlying these effects are not completely understood. In this study, we revisited the effects of GH on adipose tissue growth and lipolysis in the lit/lit mouse model. The lit/lit mice are GH deficient because of a mutation in the GH releasing hormone receptor gene. We found that the lit/lit mice had more subcutaneous fat and larger adipocytes than their heterozygous lit/+ littermates and that these differences were partially reversed by 4-week GH injection. We also found that GH injection to the lit/lit mice caused the mature adipose tissue and adipocytes to reduce in size. These results demonstrate that GH inhibits adipose tissue growth at least in part by stimulating lipolysis. To determine the mechanism by which GH stimulates lipolysis, we cultured adipose tissue explants and adipocytes derived from lit/lit mice with GH and/or isoproterenol, an agonist of the beta-adrenergic receptors. These experiments showed that whereas isoproterenol, expectedly, stimulated potent lipolysis, GH, surprisingly, had no effect on basal lipolysis or isoproterenol-induced lipolysis in adipose tissue explants or adipocytes. We also found that both isoproterenol-induced lipolysis and phosphorylation of hormone-sensitive lipase were not different between lit/lit and lit/+ mice. Taken together, these results support the conclusion that GH has lipolytic effect in mice but argue against the notion that GH stimulates lipolysis by directly acting on adipocytes or by enhancing β-adrenergic receptors-mediated lipolysis.